The postmodern city: its representation through the cyberpunk's cityscape (REVISTA NODO, 2015)
In this paper the topics covered are the technological revolution and virtuality, from the perspective of the representations of postmodern cities, incorporating to do this some visions which had arisen from literature, comics and cyberpunk film. In the second half of the 1980's it was known as the critical school of thought of postmodern science fiction, which reviewed the key elements of this new imaginary as cyberspace and virtual reality. In the context of the societies of control where the technology plays a key role. Another line is the review of the concepts of heteropia and biopower, applied to the analysis of urban space, architecture and the reading of the city from the elements that make it up, with the aim of proposing to discuss key concepts that are involved in setting up the new imaginary during the contemporary era, marked by the discussion of pivotal issues such as the postmodernity, globalisation and the so-called technological information revolution.
Keywords: postmodern cities; technological revolution; virtual city